A Public Ethics Approach Focused on the Lives of Diverse LGBTQ Homeless Youth. (2nd November 2018) - Johnson, Richard Greggory; Rivera, Mario Antonio; Lopez, Nancy
Abstract : How can an ethical-analytical framework focused on social equity help illuminate the challenges faced by lesbian, gay, bisexual, transgender, and questioning (LGBTQ) youth of color, particularly those who are homeless? The purpose of this article is to engage in just such an analysis of the complex analytical and ethical challenges presented by homelessness among LGBTQ youth. The authors take as our point of departure the premise that trans youth who are also visible minorities may be among the most marginal and most likely to experience homelessness and other threats to well-being. The authors argue that society needs to be concerned with the lives of diverse LGBTQ youth, and particularly those navigating multiple, intersecting forms of marginalization, including homelessness, because they present us with a limit situation that demands an ethical response.